2017
DOI: 10.1039/c7cc05722a
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the enhanced affinity of RNA–protein interactions triggered by RNA phosphorodithioate backbone modification

Abstract: The well-characterized interaction between the MS2 coat protein and its cognate RNA hairpin was used to evaluate changes in affinity as a result of phosphorodithioate (PS2) replacing phosphate by biolayer interferometry (BLI). A structure-based analysis of the data provides insights into the origins of the enhanced affinity of RNA-protein interactions triggered by the PS2 moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…These calculations also help explain the increased thermodynamic stability of the dithiophosphate-substituted SRL relative to the wild-type molecule, which is dominated by the enthalpic component in the experimental measurements. Taken together, these two independent studies further demonstrate the significant impact that the incorporation of dithiophosphate at strategic RNA backbone positions may have on stability and/or intermolecular interactions. By extension, the underlying reasons for the increased stability of the PS2-modified SRL also apply to the R p-PSO SRL.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These calculations also help explain the increased thermodynamic stability of the dithiophosphate-substituted SRL relative to the wild-type molecule, which is dominated by the enthalpic component in the experimental measurements. Taken together, these two independent studies further demonstrate the significant impact that the incorporation of dithiophosphate at strategic RNA backbone positions may have on stability and/or intermolecular interactions. By extension, the underlying reasons for the increased stability of the PS2-modified SRL also apply to the R p-PSO SRL.…”
Section: Discussionmentioning
confidence: 79%
“…We recently observed that regiospecific incorporation of a dithiophosphate moiety (PS2) in place of phosphate (PO2) into the backbones of RNA molecules (e.g., viral RNA and siRNA) resulted in dramatically improved binding affinities of the complexes with their respective target proteins. Anti-thrombin and anti-VEGF RNA aptamers with a single PS2 exhibited a K d of ∼1 pM or 1000-fold tighter than that of the corresponding native RNAs with thrombin and VEGF-165, respectively . Interestingly, monothiophosphate (PSO) incorporation at the same sites resulted in a much more modest gain (thrombin) or an actual loss (VEGF) of binding affinity.…”
mentioning
confidence: 99%
“…***REVISED*** 2 ammonium O,O'-diethyl dithiophosphate (DETP(S¯)=S) and 5'-Omethoxyphosphorodithioyl-2'-deoxyguanosine (G-P(S¯)=S) were selected as models (Figure 1). [14,15] Employing these compounds, ESR spectroscopy, pulse radiolysis, and theoretical calculation (Figure 1 for the radicals investigated in this work) led to several important findings: (a) Reaction of the one-electron oxidant (e.g., Cl2 •¯) with DETP(S¯)=S and G-P(S¯)=S did not result in the formation of a two-center three-electron σ 2 -σ* 1 -bonded adduct radical, P(2S∸Cl), as found for phosphorothioates. [9] Instead, oxidation of DETP(S¯)=S led to formation of a dithiyl radical, P-2S•, in which the unpaired spin is equally shared by both sulfurs.…”
Section: Full Papermentioning
confidence: 99%
“…They found that the anionic sulfur of the PS linkage makes contacts with hydrophobic and cationic amino acids. Similarly Egli showed that the related phosphorodithioate (PS2) linkage enhances binding of the MS2 coat protein and its cognate RNA hairpin by a combination of electrostatic and hydrophobic interactions . While the reports above provide insights into how a single PS can interact with proteins, structural insights into interactions of ASOs with multiple PS linkages in conjunction with additional sugar modifications are lacking.…”
Section: Introductionmentioning
confidence: 99%